ISOLATION AND CHARACTERIZATION OF CELLULOSE-DEGRADING FUNGI FROM Arachis hypogaea Shells FOR POTENTIAL BIOMASS VALORIZATION - Abdulmumini, Shakirat Afodun; Yusuf-Salihu, B. O.; Awe, S. (FUDMA JOURNAL OF SCIENCES, 2025)
The exploitation of agro-industrial waste provides a sustainable method for enzyme production and biomass use. This work examined the isolation and characterization of cellulolytic fungi from decomposed Arachis hypogaea (groundnut) shells, a lignocellulosic substrate abundant in cellulose. Four fungal isolates were procured, of which two (OPGS and OPBS) had notable cellulolytic activity, as indicated by distinct hydrolysis zones on carboxymethyl cellulose (CMC) agar stained with Congo red. The isolates were identified as Aspergillus flavus and Aspergillus niger through morphological and microscopic investigation. Quantitative screening in submerged fermentation demonstrated maximal cellulase activities of 86.7 ± 1.7 U/mL for A. flavus and 92.3 ± 1.1 U/mL for A. niger. Enzyme activity associated with a gradual decrease in pH, signifying active substrate metabolism. These findings emphasize the viability of groundnut shell as an economical substrate for cellulase production and demonstrate the appropriateness of Aspergillus strains in biomass bioconversion processes.